Transcriptomic Profiling of Fruit Development in Black Raspberry Rubus coreanus. (1st April 2018) - Chen, Qing; Liu, Xunju; Hu, Yueyang; Sun, Bo; Hu, Yaodong; Wang, Xiaorong; Tang, Haoru; Wang, Yan
Abstract : The wild Rubus species R . coreanus, which is widely distributed in southwest China, shows great promise as a genetic resource for breeding. One of its outstanding properties is adaptation to high temperature and humidity. To facilitate its use in selection and breeding programs, we assembled de novo 179, 738, 287 R . coreanus reads (125 bp in length) generated by RNA sequencing from fruits at three representative developmental stages. We also used the recently released draft genome of R . occidentalis to perform reference-guided assembly. We inferred a final 95, 845-transcript reference for R . coreanus . Of these genetic resources, 66, 597 (69.5%) were annotated. Based on these results, we carried out a comprehensive analysis of differentially expressed genes. Flavonoid biosynthesis, phenylpropanoid biosynthesis, plant hormone signal transduction, and cutin, suberin, and wax biosynthesis pathways were significantly enriched throughout the ripening process. We identified 23 transcripts involved in the flavonoid biosynthesis pathway whose expression perfectly paralleled changes in the metabolites. Additionally, we identified 119 nucleotide-binding site leucine-rich repeat (NBS-LRR) protein-coding genes, involved in pathogen resistance, of which 74 were in the completely conserved domain. These results provide, for the first time, genome-wide genetic information for understanding developmental regulation of R . coreanus fruits. They have the potential for use in breeding through functional genetic approaches in the near future.